2018
DOI: 10.1098/rspa.2017.0822
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional translation-invariant probability distributions: approximations, characterizations and no-go theorems

Abstract: We study the properties of the set of marginal distributions of infinite translation-invariant systems in the two-dimensional square lattice. In cases where the local variables can only take a small number d of possible values, we completely solve the marginal or membership problem for nearest-neighbours distributions (d = 2, 3) and nearest and next-to-nearest neighbours distributions (d = 2). Remarkably, all these sets form convex polytopes in probability space. This allows us to devise an algorithm to comput… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 28 publications
(72 reference statements)
1
19
0
Order By: Relevance
“…sym ) ⊗2k , ρ(L) 0, tr {(1,1),(2,1)} L (ρ (L) ) = tr L {(1,k),(2,k)} (ρ (L) ), SWAPρ (L) SWAP † = ρ(L) , (26) where SWAP is the operator permuting the Hilbert spaces of sites (0, y) and (1, y), for y = 0, ..., k − 1. The convergence of this hierarchy fol-lows from the proof of proposition 4 and the result, proven in [38], that any distribution P Î (a Î ) satisfying reflection symmetry along the vertical axis in addition to LTI admits a TI extension that is also symmetric with respect to vertical reflections. We arrive at the following theorem.…”
Section: D Translation Invariancementioning
confidence: 70%
See 3 more Smart Citations
“…sym ) ⊗2k , ρ(L) 0, tr {(1,1),(2,1)} L (ρ (L) ) = tr L {(1,k),(2,k)} (ρ (L) ), SWAPρ (L) SWAP † = ρ(L) , (26) where SWAP is the operator permuting the Hilbert spaces of sites (0, y) and (1, y), for y = 0, ..., k − 1. The convergence of this hierarchy fol-lows from the proof of proposition 4 and the result, proven in [38], that any distribution P Î (a Î ) satisfying reflection symmetry along the vertical axis in addition to LTI admits a TI extension that is also symmetric with respect to vertical reflections. We arrive at the following theorem.…”
Section: D Translation Invariancementioning
confidence: 70%
“…The result in [38] on the classical marginal problem generalizes to square lattices of all spatial dimensions. We arrive at the following result.…”
Section: Infinite Symmetric Scenarios Where the Entanglement Marginal Problem Is Trivialmentioning
confidence: 89%
See 2 more Smart Citations
“…For this reason, the implications of nonlocal correlations in systems consisting of a very large number of parties has been mostly lacking, despite remarkable results have been obtained throughout the years [27][28][29][30][31][32][33][34][35][36][37]. Interestingly, recent theoretical advances developed in the context of few-body Bell inequalities [38][39][40][41][42][43][44][45][46] have allowed for simple ways to detect these correlations in many-body systems. On the one hand, it has been shown that many-body observables such as the energy of the system could signal the presence of Bell correlations in the system [42].…”
Section: Introductionmentioning
confidence: 99%